Morfologia dos imaturos e do adulto de Coccidophilus citricola Brèthes (Coleoptera, Coccinellidae, Sticholotidinae), predador de cochonilhas-de-carapaça (Hemiptera, Diaspididae) de citros - Silva, Ricardo Adaime da; Almeida, Lúcia Massutti de; Busoli, Antonio Carlos [UNESP] (Sociedade Brasileira de Entomologia, 2005)
Imaturos e adultos de Coccidophilus citricola Brèthes, 1905 são descritos e ilustrados com auxílio de microscopia eletrônica de varredura. A larva é comparada com as de Microweisea Cockerel e outras espécies de Coccinellidae, e o adulto com duas espécies norte-americanas de Coccidophilus Brèthes.

Immatures and adults of Coccidophilus citricola Brèthes, 1905 are described and illustrated, using scanning electron microscopy. The larva is compared to those of Microweisea Cockerel and other species of Coccinellidae, and the adults with two North American species of the Genus Coccidophilus Brèthes.
Morphology of immatures and adult of Coccidophilus citricola Brèthes (Coleoptera, Coccinellidae, Sticholotidinae), predator of citrus armored scales (Hemiptera, Diaspididae)
Keywords: Adultos; Coccinellidae; imaturos; microscopia de varredura; Adults; Coccinellidae; immatures; Scanning electron microscopy